Trazon 3-way soil meter. [library of things]
One device, three functions. If you're a garden enthusiast and would like to be in the know of what your plants need to thrive, this soil pH meter is a must for you. No more around or relying on your green thumb. With this in-ground pH, moisture and light soil tester you'll find out whether your plants need water or not. You'll also measure the pH of your soil and the strength of the light your plants are getting. Let your plants thrive with soil pH meter moisture. Applicable both indoors and outdoors. Does your indoor gardenia plant fail to bloom? Has your monstera never grown since you brought it home from the garden center? Is your flowerbed fading and doesn't look as vibrant as your neighbor's garden? Does your lawn look like a brown carpet? Do veggies in your greenhouse look like tiny wrinkled creates? It's time to run a soil test with a soil ph test for indoor and outdoor plants and find out what your greenery is lacking.-- manufacturers description.